Pelatihan pembuatan media pembelajaran sastra Madura dengan Artificial Intelligence (AI) pada guru Madrasah Ibtidaiyah di Kabupaten Pamekasan - Romadhon, Sahrul; Alatas, Mochamad Arifin; Diningrum, Sahwa Desvita; Supandi (PERDIKAN (Journal of Community Engagement), 2025)
This community service aims to improve the competency of Madrasah Ibtidaiyah teachers in Pamekasan Regency in creating Madurese literature learning media based on Artificial Intelligence (AI). Through the Participatory Action Research (PAR) methodology, teachers are actively involved in the needs identification, planning, training implementation, and result evaluation process. This training focuses on using AI technology to create interactive and engaging learning media, expected to motivate students to understand Madurese literature. The activity results show improved teachers' understanding and skills in applying AI technology in teaching. The teachers successfully developed AI-based media that can be integrated into the Madurese literature curriculum, making the teaching and learning process more creative and effective. The impact of this activity is expected to improve the quality of Madurese literature learning and encourage teachers to continuously innovate in using technology in the classroom.[Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi guru Madrasah Ibtidaiyah di Kabupaten Pamekasan dalam membuat media pembelajaran sastra Madura berbasis Artificial Intelligence (AI). Melalui metodologi Participatory Action Research (PAR), para guru dilibatkan secara aktif dalam proses identifikasi kebutuhan, perencanaan, pelaksanaan pelatihan, dan evaluasi hasil. Pelatihan ini fokus pada penggunaan teknologi AI untuk menciptakan media pembelajaran yang interaktif dan menarik, diharapkan mampu memotivasi siswa dalam memahami sastra Madura. Hasil kegiatan menunjukkan peningkatan pemahaman dan keterampilan guru dalam mengaplikasikan teknologi AI dalam pembelajaran. Para guru berhasil mengembangkan media berbasis AI yang dapat diintegrasikan ke dalam kurikulum sastra Madura sehingga proses belajar mengajar menjadi lebih kreatif dan efektif. Dampak kegiatan ini diharapkan dapat meningkatkan kualitas pembelajaran sastra Madura dan mendorong guru untuk terus berinovasi dalam menggunakan teknologi di kelas.]